GROUP III permethylindenyl-phenoxy complexes for biorenewable polymer synthesis - Hayden, JA (2024)
Chapter One introduces the mechanism of ring opening polymerisation of cyclic esters and the importance of biodegradable and renewable polymers have in modern society. The history of organometallic synthesis is examined in the context of the evolution of asymmetric catalysts for the polymerisation. Chapter Two contains the synthesis and characterisation of PHENI* (M = Sc, Y, La, and Al) complexes with a focus on scandium. Ligand substitutions are used to synthesis initiators for ring opening polymerisation and particular consideration is given to the stereochemistry of the complexes both in solution and the solid state. Chapter Three investigates the dynamic equilibrium that are present in solution of PHENI* complexes. This chapter is designed as a guide to understanding the fluxionality of the system and the operations and mechanisms that relate the various isomeric forms. Chapter Four examines the use of PHENI* and CGC amino scandium complexes for the ROP of ϵ-caprolactone and L-Lactide homo- and co-polymerisation and mechanisms for polymerisation are explored. Coordination complexes of 4-coodinate PHENI* scandium monomer adducts of L-lactide, ϵ-caprolactone, and ω-pentadecalactone are discussed. Chapter Five details experimental procedure for all experiments in this thesis in addition to supplementary information. Chapter Six provides overall conclusions for the work in this thesis and an outlook.